Sudėtiniai rodikliai – papildomas matas Lietuvos ekonomikai įvertinti - Rukšėnaitė, Jurga (Lietuvos statistikos darbai, 2010)
In this research, a hypothesis about an additional measure that could be used as an additional tool for the analysis and assessment of economic trends in Lithuania is put forward. This additional measure has been constructed as a composite indicator, involving social and economic fields. Moreover, the paper presents business cycles, evaluated using the Hodrick–Prescott filter. For many frequently purchased products, however, it is unlikely that consumers actively process information about many brands on many attributes before making a choice. Rather, their behaviour is likely to be relatively routinized. Hence, these models are useful for explaining preference formation and indicating the most likely long-run equilibrium positions, but are not necessarily good models for repetitive decision-making.